Bridging Equity and Excellence: A Comparative Study of Waqf and Performance-Based Research Funding in Academic Library Finance - Sa’ari, Haziah; Sahak, Mohd Dasuki; Adenan, Hafiza; Goulding, Anne (International Journal of Islamic Economics and Governance, 2025)
Academic libraries are facing escalating pressures from reduced public funding, rising operational costs, and the growing need for digital innovation. As institutions seek resilient financial models, different countries have adopted varied funding mechanisms shaped by local contexts. This study offers a comparative analysis of two contrasting approaches: Malaysia’s Waqf-based model, rooted in ethical community contributions, and New Zealand’s Performance-Based Research Fund (PBRF), driven by measurable academic outputs. Using a qualitative multi-case study involving two Malaysian universities and one from New Zealand, data were gathered through interviews and document analysis. The findings indicate that Waqf provides inclusive, socially anchored support for targeted projects such as infrastructure upgrades and digital resources. However, its scalability remains limited due to rigid governance structures and its positioning as a complementary funding mechanism rather than a primary institutional source. In contrast, the PBRF enhances institutional research performance and international visibility but tends to deprioritize community engagement and equitable access. This study contributes to the discourse on sustainable library funding by proposing a hybrid framework that balances the ethical stewardship of Waqf with the structured accountability of PBRF. The findings offer practical implications for higher education leaders and policymakers navigating post-pandemic academic finance reforms, particularly in aligning institutional performance with broader societal responsibilities. © 2025 The Author(s). Licensed under CC BY-NC 4.0.